A comprehensive drug repurposing study for COVID19 treatment: novel putative dihydroorotate dehydrogenase inhibitors show association to serotonin–dopamine receptors. Issue 2 (7th January 2021) - Berber, Burak; Doluca, Osman
Abstract: Dihydroorotate dehydrogenase (DHODH) is a key enzyme required for de novo pyrimidine synthesis and it is suggested as a target for COVID19 treatment due to high pyrimidine demand by the virus replication in the infected host cells as well as its proven effect of blocking of cytokine release by the immune cells to prevent inflammation leading to acute respiratory distress. There are a number of clinical trials underway for COVID19 treatment using DHODH inhibitors; however, there are only a small number of known DHODH antagonists available for testing. Here, we have applied a methodology to identify DHODH antagonist candidates, and compared them using in silico target prediction tools. A large set of 7900 FDA-approved and clinical stage drugs obtained from DrugBank were docked against 20 different structures DHODH available in PDB. Drugs were eliminated according to their predicted affinities by Autodock Vina. About 28 FDA-approved and 79 clinical trial ongoing drugs remained. The mode of interaction of these molecules was analyzed by repeating docking using Autodock 4 and DS Visualiser. Finally, the target region predictions of 28 FDA-approved drugs were determined through PASS and SwissTargetPrediction tools. Interestingly, the analysis of in silico target predictions revealed that serotonin–dopamine receptor antagonists could also be potential DHODH inhibitors. Our candidates shared a common attribute, a possible interaction with serotonin–dopamine receptors as well as other oxidoreductases, like DHODH. Moreover, the Bruton Tyrosine Kinase-inhibitor acalabrutunib and serotonin–dopamine receptor inhibitor drugs on our list have been found in the literature that have shown to be effective against Sars-CoV-2, while the path of activity is yet to be identified. Identifying an effective drug that can suppress both inflammation and virus proliferation will play a crucial role in the treatment of COVID. Therefore, we suggest experimental investigation of the 28 FDA-approved drugs on DHODH activity and Sars-CoV-2 virus proliferation. Those who are found experimentally effective can play an important role in COVID19 treatment. Moreover, we suggest investigating COVID19 case conditions in patients using schizophrenia and depression drugs.